A Participatory Survey to Investigate the Long-Term Effectiveness of Adult Psychiatric Services (PSILEAPS): Baseline Data and Recruitment Experiences. - Bergström, Tomi; Gauffin, Tapio; Hietasaari, Teija; Koivuniemi, Nina; Leinonen, Anne; Öfverberg, Enni; Viitakoski, Reetta; Haaraniemi, Timo; Partanen, Katja; Rantamaa, Katariina; Yrjänheikki, Vilhelmiina; Jauhiainen, Tiina; et al. (Community Mental Health Journal, 2025)
In clinical psychology and psychiatry, traditional hypothesis testing is challenging due to the subjective and contextual nature of the studied phenomenon. To address this, more exploratory and participatory research is needed. This paper reports recruitment experiences and baseline data of a prospective exploratory cohort study with participatory elements, initiated in mental health services in one Finnish region. The primary aims, design, and survey for data collection were developed through community meetings involving local mental health workers, peer experts, and service users. Over 2 weeks, all mental health service users, their care teams, and social network members were asked to share their views on the reasons for needing services and what aspects of treatment have been or could be helpful or unhelpful. Descriptive statistics summarized baseline data, and simple thematic analysis examined field notes on supporting and hindering aspects of the study design. A total of 117 service users, 54 care team members, and 34 social network members participated, with a service user attrition rate of 40–50%. The study achieved 79% of the target sample size. Women and participants with mood disorder diagnoses and long-term service usage were overrepresented. Findings suggest that integrating participatory research into Finnish public mental health services would require additional resources. Despite its limitations, the collected data will facilitate exploratory research into real-life mental health treatment processes from various perspectives.